2021
DOI: 10.1101/2021.08.10.455855
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polysorbate 80 Controls Morphology, Structure and Stability of Human Insulin Amyloid-Like Spherulites

Abstract: Amyloid protein aggregates are not only associated with neurodegenerative diseases and may also occur as unwanted by-products in protein-based therapeutics. Surfactants are often employed to stabilize protein formulations and reduce the risk of aggregation. However, surfactants alter protein-protein interactions and may thus modulate the physicochemical characteristics of any aggregates formed. Human insulin aggregation was induced at low pH in the presence of varying concentrations of the surfactant polysorba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 94 publications
3
6
0
Order By: Relevance
“…Aggregates consisting of misfolded proteins and amyloid-like structure may result in the break of immune tolerance in transgenic mice [39]. Amyloid-like spherulites produced in acetic acid contain a high amount of aggregated β-sheet, compared to native human insulin [11, 14], thus reducing the amount of aggregated β-sheet present in the spherulite could potentially reduce the immunogenicity risk of this aggregate type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregates consisting of misfolded proteins and amyloid-like structure may result in the break of immune tolerance in transgenic mice [39]. Amyloid-like spherulites produced in acetic acid contain a high amount of aggregated β-sheet, compared to native human insulin [11, 14], thus reducing the amount of aggregated β-sheet present in the spherulite could potentially reduce the immunogenicity risk of this aggregate type.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several aggregates formed in vitro are generated in formulations, which are not suitable for certain characterization techniques or are not readily translatable to biological assays. Solvent exchange is thus required to allow for characterization or application in biological assays and it is often achieved via centrifugation-and dialysis-based methods [12][13][14]. Morphological integrity before and after solvent exchange is assumed intact, yet rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that the addition of PS80 slows down the insulin amyloid aggregation process 19 . With the aim of determining how PS80 affects the energy barrier associated with the transition of soluble insulin to the aggregated form, we used the amyloid-specific dye Thioflavin T (ThT) 21 to detect the bulk aggregation kinetics at different temperatures in the range 37–60 °C.…”
mentioning
confidence: 99%
“…In a previous study, we identified a surprising effect of the commonly used surfactant polysorbate 80 (PS80) on the stability and aggregation propensity of insulin in solution 19 . More specifically, it was shown that PS80 slows down the thermal aggregation of insulin, but induced the formation of highly stable spherulites with an increased content of β-sheet structure and increased protein packing density 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation